Prolonged ozone exposure in an allergic airway disease model: Adaptation of airway responsiveness and airway remodeling - Park Chang-Soo; Lee Jae-Hyuk; Choi Inseon-S; Jang An-Soo; Park Choon-Sik (Respiratory Research, 2006)
Abstract Background Short-term exposure to high concentrations of ozone has been shown to increase airway hyper-responsiveness (AHR). Because the changes in AHR and airway inflammation and structure after chronic ozone exposure need to be determined, the goal of this study was to investigate these effects in a murine model of allergic airway disease. Methods We exposed BALB/c mice to 2 ppm ozone for 4, 8, and 12 weeks. We measured the enhanced pause (Penh) to methacholine and performed cell differentials in bronchoalveolar lavage fluid. We quantified the levels of IL-4 and IFN-γ in the supernatants of the bronchoalveolar lavage fluids using enzyme immunoassays, and examined the airway architecture under light and electron microscopy. Results The groups exposed to ozone for 4, 8, and 12 weeks demonstrated decreased Penh at methacholine concentrations of 12.5, 25, and 50 mg/ml, with a dose-response curve to the right of that for the filtered-air group. Neutrophils and eosinophils increased in the group exposed to ozone for 4 weeks compared to those in the filtered-air group. The ratio of IL-4 to INF-γ increased significantly after exposure to ozone for 8 and 12 weeks compared to the ratio for the filtered-air group. The numbers of goblet cells, myofibroblasts, and smooth muscle cells showed time-dependent increases in lung tissue sections from the groups exposed to ozone for 4, 8, and 12 weeks. Conclusion These findings demonstrate that the increase in AHR associated with the allergic airway does not persist during chronic ozone exposure, indicating that airway remodeling and adaptation following repeated exposure to air pollutants can provide protection against AHR.